Organizational Affective Commitment Mediates the Relationship Between Transformational Leadership and Turnover Intention - Prastikawati, Nevelona; Herachwati, Nuri; Muzakki, Muzakki (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Turnover intention is a phenomenon that has garnered attention in today's workplace environment. It refers to individuals' desire to leave their current jobs in the near future. This phenomenon is significant as it can impact organizational stability, recruitment costs, and employee productivity. The aim of this study is to assess the influence of transformative leadership on turnover intention and affective commitment. The role of affective commitment as a mediator is also examined in this research. A quantitative research approach is employed, and the sample size consists of 160 participants from a total population of 255 individuals. Several departments participated in this study, including Accounting, Operations, Marketing and Sales, Recruitment, Human Resources, Treasury, IT Management, and Support Departments. To evaluate the hypotheses, this investigation utilizes a data analysis technique known as Partial Least Squares (PLS). The findings of this research indicate that there is substantial evidence showing that transformative leadership negatively impacts employees' intention to resign from their current positions and positively influences affective commitment. Furthermore, it is revealed that affective commitment serves as a mediator between the correlation of transformative leadership and employees' inclination to resign from their roles. This study examines practical implications as well as relevant research recommendations pertaining to the core issue.